About the national health policy to indian peoples, at the "500 years" commemorations - Varga, István Van Deursen; Adorno, Rubens de Camargo Ferreira (Journal of Health Law, 2001)
We rememorate and analise the facts, events and refereal documents related to the national Indian health policy, of the last twenty years, in order to embed a reflection about its contemporary directions and tendencies, from the perspective of the I and II National Health Conferences to the Indian Peoples on. We also discuss the interests and roles of the main institutions and political forces acting in this scenario, enfasizing the necessity and the importance of the realization of the III National Health Conference of the Indian Peoples.